Pengaruh Hatha Yoga Terhadap Kesehatan Mental Anak-Anak Anggota Sanggar Samirata - Juniartha, Made G.; Suputra, I Kadek Darmo; Maitrya, Ni Putu Maha Anjali (Jayapangus Press, 2024)
The mental health of the children of Sanggar Samirata members tends to be poor. The poor mental health of the children of Sanggar Samirat members is characterized by stress, anxiety, and emotional instability. Hatha yoga is a non-pharmacological intervention that can help control thoughts and emotions, and improve health holistically. This study aimed of this study was to determine the effect of hatha yoga on the mental health of the children of Sanggar Samirata members. This study used an experimental method with a one group pretest-posttest experimental design. The population of this study was 23 children of Sanggar Samirata members. The sampling technique used was total sampling. The data collection method used self-report with a data collection tool in the form of an inventory, namely the Brief Mental Health Inventory (BMHI-12). This measuring instrument had a Cronbach alpha reliability level of 0.824. Hatha yoga intervention was given in 16 meetings. Hatha yoga was given twice every week with a duration of 2 hours each meeting. Hatha yoga intervention was given by yoga instructors who had competence in their field. Data analysis techniques in this study used paired sample t-test, with the data normality assumption test performed first. Different tests results in this study showed a t-value of -5.971 with a significance of 0.000 (P <0.05). It meant that there was an influence of hatha yoga on the mental health of the children of Sanggar Samirata members.